Experimental Study and Damage Effect Analysis of Concrete Structures under the Combined Loadings of Penetration and Explosion. (30th May 2020) - Geng, Hao; Lu, Hao; Sun, Shanzheng; Yue, Songlin; Song, Chunming; Feng, Shufang
Abstract : The penetration-explosion warhead is one of the most effective weapons for use against concrete structures. In order to study the phenomena and results for concrete damage caused by the combined effects of penetration and explosion, field experiments were performed on damaged concrete targets with different penetration speeds and explosive charges. The damage to the targets was analyzed, the causes were determined, and prediction methodologies were developed. Dimensional analysis was used to fit experimental results, a formula for calculating the damage depth and volume was proposed, and the dependence of the damage depth and volume on the aspect ratio of the explosive (or charge) and the kinetic energy of bullet penetration were determined. For a given projectile size and quantity of explosives, the damage depth and volume of the concrete target increase with the increasing projectile impact coefficient, but this trend gradually decreases. This observation can also provide a reference for the optimal design of penetration-explosion warheads, exhibiting the desired performance-price ratio.